(untitled) (Academicia Globe: Inderscience Research, 2022)
The main purpose of the scientific article is to present the result of the improvement of the banking system of the republic, based on international experience, innovative ideas and market-methodological framework. In this scientific plot the theoretical and practical basis for the application of innovative technologies in the banking payment system, the factors influencing it, the practical measures taken by the country’s commercial in this direction. Thera also proposals and scientific conclusions on the development of digital services in the banking system of the republic with the help of innovative technologies.